The artistic potential of the Künstlerroman genre (a novel about an artist) in Irish modern literature and the transformation of the author’s ideological style translated into Ukrainian based on J. Joyce’s “Portrait of an Artist as a Young Man” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
Art of the ХХ century, in particular literature, developed under the influence of modernism. The personification of artistic research and experiments in the literature of this era was the figure of the famous Irish writer J. Joyce. Joyce’s artistic heritage has long been one of the most interesting and attractive phenomena for literary critics in various schools and industries. In modern researches of Ukrainian scientists, Joyce’s works are considered in a broad ideological and aesthetic context of that time, its innovation in the context of the development of literary trends of the last century. The paper is devoted to the study of the features of the translation of the autobiographical novel by the Irish writer James Joyce’s “A Portrait of the Artist as a Young Man” and the reproduction of the writer’s idiostyle by Mariana Prokopovych. The first chapter defines the theoretical foundations for studying the features of translation of autobiographical works; analyzes the problem of determining the genre of the novel about an artist; considers Künstlerroman as a modern literary and linguistic phenomenon. In the research part of the article, the features of translating an autobiographical novel are presented; the novel about an artist “A Portrait of the Artist as a Young Man” in the literary heritage of James Joyce is analyzed; the transformation of James Joyce idiostyle in the translation into Ukrainian of the Künstlerroman novel “A Portrait of the Artist as a Young Man” is taken under consideration: lexical aspect of equivalence: denotative aspect of lexical transformations and connotative aspect of lexical transformations; lexical-grammatical aspect of equivalence; grammatical aspect of equivalence, in particular, transformation at the morphological and syntactic levels. “Portrait of a young artist” is, in our opinion, the key work that combines the world of a novice writer with a deep philosophical view of the world of a mature artist. The author of the article is convinced that the problems of adequacy and equivalence of the original text and translation, without a doubt, deserve further research in modern translation studies, the prospects for further research in the context of our subject are, in our opinion, the ability to analyze functional-communicative, stylistic, connotative phraseological, onomasiological and pragmatic equivalence of translations into Ukrainian of other works by Irish writer J. Joyce and novels by other authors in the genre of the novel about the artist.
Keywords: a novel about an artist; autobiographical novel; translation; idiostyle; denotative aspect of translation; connotative aspect of translation; translation transformati